The Photoshop and Painter artist tablet book : creative techniques in digital painting using Wacom and the iPad - Threinen-Pendarvis, Cher (Peachpit Press, 2014)
"Artists today use digital tools that allow them to work as naturally and spontaneously as if they were using traditional artist tools such as pastels, watercolors, oil media, and gouache. With the recent growth of the tablet market, there are more tools and more sophisticated features available now than ever before and an increased desire by artists to learn how to use them. As much art book as guide, The Photoshop and Painter Artist Tablet Book uses traditional drawing and painting theory exercises, coupled with real life projects, to show readers how they can use Painter and Photoshop with pressure-sensitive tablets for beautiful results. Award-winning artist and author Cher Threinen-Pendarvis takes readers through a variety of projects designed to improve their drawing, composition, and conceptual thought processes while exploring different uses of the many brushes available in Painter and Photoshop. Among many valuable concepts and techniques you'll learn to: create tonal, gestural, and contour drawings with a pressure-sensitive tablet and stylus; use the iPad for sketching out ideas and use related software including Brushes, ArtStudio, Sketchbook Pro, Procreate, Adobe Ideas, and Adobe PS Touch; translate traditional color theory to digital color tools; and incorporate scanned artwork into digital paintings and use photos as a reference for illustrations."--Publisher's description.